GLOBALIZATION ANALYSIS BENEFIT OR INJURY - Zambrano Cabrera, Shakira Pamela (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
“Globalization has caused great confusion, especially in those countries where thousands of economies have been devastated by this phenomenon. It was curious, however, that globalization had not acted equally in all countries. But the suffering of third world countries far exceeded the pain required to enter the globalized world; it was impossible for these countries not to react to the inequality of the world trading system which requires opening the doors of their markets to bring in the products of the first world, This only caused more wealth for the rich and more poverty and anger for the poor.   Currently everything limits physical contact, in wars bombs are dropped from 15000 meters of height, just as economic policies are thought and implemented by people residing in a 5 star hotel, far from the people who will be destroyed; the World Bank“s motto is “Our dream is a world without poverty”. Translated into numbers, some 1.2 billion people live on less than one dollar a day and 2.5 billion people live on less than two dollars a day, making up more than 60% of the worldss population.